Death and the car: on (auto)mobility, violence, and injustice - Culver, Gregg (ACME, 2018)
Despite the incredible and highly socially unjust killing power of the car and its impacts on urban life, the relationship between (auto)mobility, violence, and justice has been neglected in much of human geography - critical or otherwise. Toward addressing this gap, I first suggest a basic framework for conceptualizing the general relationship between (auto)mobility and violence. Then, using the empirical example of the United States as a society dominated by automobility, I outline some of the injustices of vehicular violence (or the violence bound up with automobility), especially from the perspective of the city. In so doing, I have three main goals. First, I aim to contribute toward a discussion of transport justice within an emerging, more critical urban transport geography. Second, I hope to spark greater attention within critical geography to (auto)mobility in general, and to the relationship between (auto)mobility, violence, and justice in particular. Finally, I seek to make the case that vehicular violence should be an urgent target of action both within and outside of academia, and that it should be more widely addressed within broader struggles for the just, sustainable, and livable city.
Gesehen am 25.08.2022